Effect of pH Variations in Eosin Methylene Blue Agar (EMBA) Medium on E. coli Growth - Lestari, Diah; Haliza, Eva Nur; Setiawan, Heru (JURNAL INFO KESEHATAN, 2024)
The growth of E. coli is influenced by several factors, including environmental pH. Environmental pH unsuitable for bacterial growth conditions will interfere with the enzyme activity and influence bacterial growth. This study aimed to determine the effect of pH variations (5.3, 5.8, 6.3, 7.3, 7.8, 8.3) in EMBA medium on E. coli growth. The research method used was true experiment post-test-only control design. The samples in this study were suspensions with dilutions of 10-4, 10-5, 10-6, and 10-7, inoculated using the duplo test to EMBA with various pH conditions, so that the total sample size is 48. The results showed that the mean number of E. coli bacteria on EMBA with pH 5.3 was 9.1 x 106 CFU/mL; with pH 5.8 was 9.6 x 106 CFU/mL; with pH 6.3 was 1.2 x 107 CFU/mL; with pH 7.3 was 1.1 x 107 CFU/mL; with pH 7.8 was 9.7 x 106 CFU/mL; and with pH 8.3 was 7.1 x 106 CFU/mL. Growth in positive control showed the mean number 1.4 x 107 CFU/mL; negative control showed no growth of E. coli or other microorganisms. Based on the One-Way ANOVA statistical test with a 95% confidence level, there was no difference in the mean number of E. coli bacteria in the six pH variations of EMBA medium (p-value > 0.05). E. coli bacteria grew best at neutral pH. Its growth decreases in slightly acidic and slightly alkaline pH, but it can still be observed. This allows E. coli to survive in extreme pH. Pathogenic E. coli have developed the potential to live inside the human body. They will experience temporary stress in unfavourable conditions before finally adapting. The advice for future researchers is to test the effect of pH on E. coli growth by using other E. coli growth media or with a wider range of pH (more acidic and more basic). It is also recommended to conduct further research about the effect of various environmental conditions such as temperature, nutrients, and others on bacterial growth.